Contribuţii la bibliografia românească veche - Bogdan Andriescu (Revista de Istorie și Teorie Literară)
This paper aims to present the results of our research of the Old Romanian book entered upon three institutions of culture: The ASTRA County Library in Sibiu, The Széchényi National Library, The Eötvös Loránd University Library in Budapest. The Széchényi National Library in Budapest and the Eötvös Loránd University Library in Budapest hold an important old Romanian stock of books. The study includes old Romanian book unknown to the Romanian bibliographical sources detected in the collections of the three institutions mentioned above. Mention must be made that we had into account three categories of books: old Romanian book unknown to the bibliographical resources, book known to the bibliographical sources only at the informational level (there has not been detected any copy; known copies without a complete bibliographical description); old Romanian book detected at the informational level, without the identification of any copy.